PHYSIOLOGICAL CHARACTERIZATION AND CONSERVATION OF SEEDS OF Eugenia candolleana (MYRTACEAE) - Pirola, Kelli; Dotto, Marcelo; Cassol, Darcieli Aparecida; Júnior, Américo Wagner; Mazaro, Sérgio Miguel; Citadin, Idemir (REVISTA DE AGRICULTURA, 2018)
The objective of this work was to study the physiological behavior of Eugenia candolleana seeds. The work was conducted at the â€œUniversidade TecnolÃ³gica Federal do ParanÃ¡ - Campus Dois Vizinhos State of ParanÃ¡â€. Reducing the moisture content of the seeds reduced their viability but it should not be reduced by more than 20% of its initial content. E. candolleana seeds did not present dormancy. The use of sulfuric acid in both photoperiod conditions is not recommended.